Rapid radiations underlie most of the known diversity of life - Wiens, John J.; Moen, Daniel S. (Frontiers in Ecology and Evolution, 2025)
Rapid radiations, including adaptive radiations, are of considerable interest to evolutionary biologists, in large part because they are thought to underlie much of the species diversity of life. Yet, this fundamental idea has only been tested at a limited scale, within frogs. Here, we test this idea across living organisms and within many of the largest clades (e.g. animals, plants). Specifically, we quantify how much of Earth’s species richness is contained within rapid radiations (clades with high net diversification rates). We find that among the major clades of living organisms and among land plant phyla and animal phyla, >80% of known species richness is contained within the few clades in the upper 90th percentile for diversification rates in each group. Thus, these exceptionally rapid radiations contain most of Earth’s extant species diversity. Patterns were broadly similar using smaller clades (orders, families) and in insects and vertebrates, with the majority of species generally contained within clades in the upper 75th percentile. Results were also similar using large-scale clades defined by their ages instead of taxonomic ranks. Overall, these results show for the first time that most of the known species richness of life is explained by rapid radiations. Moreover, phenotypic evidence from previous studies suggests that some of the most species-rich rapid radiations across life, animals, and plants may also qualify as adaptive radiations.